PENINGKATAN KETERAMPILAN MENULIS KARANGAN NARASI DENGAN MENGGUNAKAN MEDIA AUDIOVISUAL DAN METODE QUANTUM LEARNING - Ahsin, Muhammad Nur (Universitas Muria Kudus, 2016)
The Increase in the Narrative Writing Skills Using Audiovisual Media and Method ofQuantum Learning (Classroom Action Research on the students of Class XA Islamic HighSchool TBS Kudus Academic Year 2013/2014). The aims of this research are to: (1) improve thequality of the learning process to write narrative using audiovisual media and quantum learningmethod XA grade student of MA (Islamic High School) Tasywiquth Thullab Salafiyyah (TBS)Kudus and (2) improving the writing narrative skills using audiovisual media and methods ofquantum learning XA grade student of MA (Islamic High School) TBS. The Method used thisresearch use qualitative research methods, in the form of Classroom Action Research. Subjectof this research in Indonesian Teachers and student of Class X A a Islamic High Scholl (MA)TBS. Datta was collected by way of: observation, interviews, review of documents, andnarrative writing skills test. Test the validity of using triangulation of data sources andtriangulation methods. The research proces was conducted in two cycles, each consisting offour stages: (1) preparation, (2) action, (3) observation and evaluation, (4) analysis andreflection.The results are: (1) the aplication of audiovisual media and quantum learning methodscan improve the quality of learning to write narrative on the class X A Islamic High Scholl(MA) TBS Kudus, (2) the use of audiovisual media and quantum learning methods to improvethe skills narrative writing in the class X A Islamic High Scholl (MA) TBS Kudus. This can be seen with the increase in students activity, student attention to the teacher's explanations, as well as the independence of student when writing narrative. In addition, the average studentwho experienced complete learned from the first cycle an second cycle also incresed. the abilityto write narrative essays of students increased, the average value of the first cycle 73.46, whilein the second cycle increased to 80.89.